Beggar Thy Neighbour: Exchange Rate Regime Misadvice from Misunderstandings of Mundell (1961) - Robin Pope (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
Economists invoke Mundell (1961) in arguing for the general policy of a flexible exchange rate regime as a means of restoring equilibria after shocks. But there is a discrepancy between the intent of the general policy and attempts at its implementation as identified by specific changes in exchange rates. When we assemble the set of specific changes called for by distinct economists operating as advocates for individual countries, these are uniformly in the form of beggar-thy-neighbour advice ie travesties of objectively identifying disequilibria and a menace to international cooperation and peace. This paper traces the unintended travesties to problems of complexity and uncertainty, problems that implicitly are assumed absent in Mundell (1961) rendering the situation so simple that equilibria are transparent. The problems remained essentially unaddressed when economists extended Mundell (1961) via expected utility theory since this theory also ignores the impossibility of maximising and the complexities of central bankers, private firms and others in doing the evaluation stage in reaching decisions. The problems can be overcome by modelling within SKAT, the Stages of Knowledge Ahead Theory. This paper points to experimental evidence in support of the view that under all sorts of disequilibrating shocks, currency unions outperform flexible currencies by eliminating the inefficiencies generated by exchange rate uncertainty.
Keywords: F31; D80; 330; optimal currency area; exchange rate regime; certainty; uncertainty effects; beggar-thyneighbour policies; SKAT; Optimaler Währungsraum; Wechselkurssystem; Konjunkturzusammenhang; Mundell-Fleming-Modell; Theorie